Implementasi Algoritma Dijkstra untuk Pencarian Rute Terpendek Menuju Rumah Sakit pada Aplikasi C-Hos (Covid-19 Hospital) - Muhammad Taufiq Ismail; Septi Andryana; Aris Gunaryati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Exactly on March 2, 2020, the corona virus (Covid-19) entered Indonesia. In Jakarta, there were 445,302 positive cases of Covid-19 as of June 12, 2021. The government itself has appointed Wisma Athletes as an emergency corona hospital and there are also several hospitals in Jakarta to serve as COVID-19 referral hospitals However, many people do not know the referral hospital for COVID-19. This is very unfortunate, because at any time people or residents who have shown symptoms of Covid-19 can immediately come to the nearest Covid-19 referral hospital. From this problem, an Android-based C-Hos (Covid-19 Hospital) application was created by applying the Dijkstra Algorithm to search for the shortest route to the covid-19 referral hospital. Based on the results of testing 20 times, the accuracy of the shortest route to the Covid-19 referral hospital on the C-Hos application is 100%.